142k views
1 vote
OMG HELP PLEASE!!!!!!!!!!

OMG HELP PLEASE!!!!!!!!!!-example-1

2 Answers

3 votes

Explanation:

Here,


= ( √(12) )/( √(3) + 3)

is given.

Now, rationalizing it,


= ( √(12) )/( √(3) + 3) * ( √(3) - 3 )/( √(3) - 3)

now, simplifying it,


= \frac{ √(12 ) * √(3 ) - 3 }{( { √(3) )}^(2) - 9}

or, simplifying it we get,


= (3)/( - 6)

= 1/ -2

Hope it helps...

User Irtaza
by
5.0k points
2 votes

Answer:

Explanation:

Hello, please consider the following.

We will multiply the numerator and denominator by


3-√(3) to get rid of the root in the denominator.

Let's do it!


\begin{aligned}(√(12))/(√(3)+3)&=(√(2^2*3)*(3-√(3)))/((3+√(3))*(3-√(3)))\\\\&=(2√(3)*(3-√(3)))/(3^2-√(3)^2)\\\\&=(2√(3)*(3-√(3)))/(9-3)\\\\&=(2√(3)*(3-√(3)))/(6)\\\\&=(6√(3))/(6)-(2*3)/(6)\\\\&=√(3)-1\\\\\large &\boxed{=-1+√(3)}\\\end{aligned}

Thank you

User BlackHoleGalaxy
by
5.0k points